Economic and legal nature of digital assets managed by autonomous AI agents - Gorgiladze, Nodari (Здобутки економіки: перспективи та інновації, 2025)
The article is devoted to justifying the economic and legal nature of digital assets operating under the control of autonomous AI agents. The purpose of this study is to develop a generalizing conceptual model that integrates the mechanisms of creating and circulating digital value with legal approaches to determining ownership, responsibility, and regulatory control in digital environments characterized by high autonomy. The methodological basis of the study is an interdisciplinary analysis, structural-logical generalization, a comparative legal approach, and institutional analysis of the regulatory models of the EU and Ukraine. Elements of the theory of digital capital and the concept of decentralized management are used to interpret the market behavior of AI agents. Results. It is determined that digital assets under the control of AI agents function as hybrid economic and legal entities, where the source of value is algorithmic processes of transaction optimization, forecasting and autonomous decision-making. It is shown that the European regulatory field forms a holistic model of harmonization of technological autonomy and responsibility (MiCA, AI Act, UNIDROIT Principles). Ukrainian legislation focuses on defining a digital asset as an object of civil rights and does not cover the agency of artificial intelligence. The proposed conceptual model demonstrates the interdependence of economic (creation, monetization, value circulation) and legal (ownership, accountability, enforcement) aspects of digital assets managed by artificial intelligence. Conclusions. The analysis made it possible to establish that digital assets managed by autonomous AI agents form a dual economic and legal regime, in which algorithmic value creation is inextricably linked to the legal consolidation of ownership and responsibility rights. The harmonization of these two dimensions is a key outcome of the study and provides a basis for the development of state policy in the digital economy field. Further research should focus on developing mechanisms for algorithmic responsibility and adapting the national regulatory framework to European standards, taking into account the participation of autonomous AI agents in market processes.